2023
DOI: 10.1101/2023.02.27.526590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenome-assembled microbial genomes from Parkinson’s disease fecal samples

Abstract: The human gut microbiome composition has been linked to Parkinson’s disease (PD). However, knowledge of the gut microbiota on the genome level is still limited. Here we performed deep metagenomic sequencing and binning to build metagenome-assembled genomes (MAG) from 136 human fecal microbiomes (68 PD samples and 68 control samples). We constructed 952 non-redundant high-quality MAGs and compared them between PD and control groups. Among these MAGs, there were 22 different versions ofCollinsellaandPrevotellaMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In addition, studies have reported the existence of CRISPR-Cas systems in phages, confering a survival advantage to the host organism (ref 27 Seed et al, 2013). Interestingly, 33% of these viral contigs were also found within a metagenome-assembled genome (MAG) constructed from the same dataset in our earlier study (ref 54 Duru et al, 2023), suggesting the possibility that the cas defense systems in these MAGs may have been acquired from the phages. Finally, we have noted the presence of several CRISPR arrays within the viral contigs, lacking any cas genes, with the majority consisting of less than three repeats.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, studies have reported the existence of CRISPR-Cas systems in phages, confering a survival advantage to the host organism (ref 27 Seed et al, 2013). Interestingly, 33% of these viral contigs were also found within a metagenome-assembled genome (MAG) constructed from the same dataset in our earlier study (ref 54 Duru et al, 2023), suggesting the possibility that the cas defense systems in these MAGs may have been acquired from the phages. Finally, we have noted the presence of several CRISPR arrays within the viral contigs, lacking any cas genes, with the majority consisting of less than three repeats.…”
Section: Discussionmentioning
confidence: 53%
“…Previously a gut virome study also reported that “lysogenic” type viruses do not dominate the gut ecosystem (ref 67 Bhardwaj et al, 2022). In our earlier study, we found that about 28% of the predicted viral sequences are actually part of microbial genomes (ref 54 Duru et al, 2023). Possibly, the high number of “lytic” viruses might explain why there were relatively few phages within the microbial genomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation